Induction of apoptosis and regulation of MicroRNA expression by (2E,6E)-2,6-bis-(4-hydroxy-3-methoxybenzylidene)-cyclohexanone (BHMC) treatment on MCF-7 breast cancer cells - Yeap, Swee Keong; Norlaily, Mohd Ali; Akhtar, Muhammad Nadeem; Nursyamirah, Abd Razak; Chong, Zhi Xiong; Ho, Wan Yong; Boo, Lily; Seema, Zareen; Tonni Agustiono, Kurniawan; Avtar, Ram; Ng, Stephanie Y. L.; Ong, Alan Han Kiat; et al. (MDPI - Open Access Publishing, 2021)
(2E,6E)-2,6-bis-(4-hydroxy-3-methoxybenzylidene)-cyclohexanone (BHMC) is a synthetic curcumin analogue, which has been reported to possess anti-tumor, anti-metastatic, and anti-invasion properties on estrogen receptor (ER) negative breast cancer cells in vitro and in vivo. However, the cytotoxic effects of BHMC on ER positive breast cancer cells were not widely reported. This study was aimed to investigate the cytotoxic potential of BHMC on MCF-7 cells using cell viability, cell cycle, and apoptotic assays. Besides, microarray and quantitative polymerase chain reaction (qPCR) were performed to identify the list of miRNAs and genes, which could be dysregulated following BHMC treatment. The current study discovered that BHMC exhibits selective cytotoxic effects on ER positive MCF-7 cells as compared to ER negative MDA-MB-231 cells and normal breast cells, MCF-10A. BHMC was shown to promote G2/M cell cycle arrest and apoptosis in MCF-7 cells. Microarray and qPCR analysis demonstrated that BHMC treatment would upregulate several miRNAs like miR-3195 and miR-30a-3p and downregulate miRNAs such as miR-6813-5p and miR-6132 in MCF-7 cells. Besides, BHMC administration was also found to downregulate few tumor-promoting genes like VEGF and SNAIL in MCF-7. In conclusion, BHMC induced apoptosis in the MCF-7 cells by altering the expressions of apoptotic-regulating miRNAs and associated genes.